2017
DOI: 10.1037/xhp0000415
|View full text |Cite
|
Sign up to set email alerts
|

Neighing, barking, and drumming horses—object related sounds help and hinder picture naming.

Abstract: The study presented here investigated how environmental sounds influence picture naming. In a series of four experiments participants named pictures (e.g., the picture of a horse) while hearing task-irrelevant sounds (e.g., neighing, barking, or drumming). Experiments 1 and 2 established two findings, facilitation from congruent sounds (e.g., picture: horse, sound: neighing) and interference from semantically related sounds (e.g., sound: barking), both relative to unrelated sounds (e.g., sound: drumming). Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 88 publications
13
48
1
Order By: Relevance
“…In a recent study we tested this proposed specificity of the effect by using environmental distractor sounds instead of distractor words (e.g., BARKING horse vs. DRUMMING drum , when the picture shows a horse; Mädebach et al, 2017). We likewise observed semantic interference, which shows that semantic interference is not restricted to tasks that involve distractor words.…”
Section: Semantic Interference From Distractor Sounds In Picture Namingmentioning
confidence: 74%
See 3 more Smart Citations
“…In a recent study we tested this proposed specificity of the effect by using environmental distractor sounds instead of distractor words (e.g., BARKING horse vs. DRUMMING drum , when the picture shows a horse; Mädebach et al, 2017). We likewise observed semantic interference, which shows that semantic interference is not restricted to tasks that involve distractor words.…”
Section: Semantic Interference From Distractor Sounds In Picture Namingmentioning
confidence: 74%
“…In a recent study (Mädebach, Wöhner, Kieseler, & Jescheniak, 2017) we observed that semantically related environmental distractors sounds (e.g., BARKING dog ) interfere with picture naming (e.g., "horse^) more strongly than unrelated environmental distractor sounds (e.g., DRUMMING drum ). This semantic interference effect from distractor sounds resembles the one typically obtained with distractor words, which has been central for the debate on the mechanism of lexical selection.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Just as modality-specific (e.g., Mulatti, Treccani, & Job, 2014;Vermeulen, Corneille, & Niedenthal, 2008) and category-specific (e.g., Madebach, Wohner, Kieseler, & Jescheniak, 2017) information can yield varying grounding effects across perceptual dimensions, so can effector-specific words affect processes in the motor domain. Note, however, that action mechanisms possess unique functional features (Prinz, Beisert, & Herwig, 2013;Shadmehr, Smith, & Krakauer, 2010;Shin, Proctor, & Capaldi, 2010), so that their interaction with higher-order operations may not be directly inferred from perception-oriented studies.…”
Section: Introductionmentioning
confidence: 99%